2012
DOI: 10.3109/00365599.2012.681062
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic extended pelvic lymphadenectomy for staging can be performed with limited morbidity and short hospital stay in patients with prostate cancer

Abstract: Laparoscopic extended pelvic lymphadenectomy can be performed with minimal significant complications and short hospital stay in patients with high-risk prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…One study reported standardized complications after laparoscopic staging PLND. 12 In 133 high-risk PCa patients, Liedberg et al reported 26% grade 1, 8% grade 2 and 2% grade 3 complications, which is in line with the present results (10%, 3% and 6% respectively). The fact that both our studies showed no grade 4-5 complications underlines the safety of this MI surgery.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…One study reported standardized complications after laparoscopic staging PLND. 12 In 133 high-risk PCa patients, Liedberg et al reported 26% grade 1, 8% grade 2 and 2% grade 3 complications, which is in line with the present results (10%, 3% and 6% respectively). The fact that both our studies showed no grade 4-5 complications underlines the safety of this MI surgery.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that both our studies showed no grade 4-5 complications underlines the safety of this MI surgery. 12 Additionally, we compared MI-with O-PLND (n = 43). With MI-PLND we saw fewer postoperative grade 3 complications (6% vs 16% with O-PLND), although this numerical difference was not statistically significant (P = 0.100).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations